La administración educativa en el desempeño del talento humano de la escuela de Educación General Básica "Valencia Herrera" correspondiente a la zona 9, distrito 7, circuito 17 D07 en el año lectivo 2015-2016. Estrategias de liderazgo en los procesos administrativos. - Guacapiña Toapanta, Alexandra Elizabeth (2016)
In the absence of leadership in institutional administrative processes facing the elementary school "Valencia Herrera" arises to strengthen educational administration through strategies that improve the performance of the talent of the establishment by analyzing and taking action that lead to substantially improve the academic environment in which daily interact members of the educational community , accordingly to comply with such action applies a methodology with quantitative approach since it is allows to observe the causes and effects of research and in turn approves make transition by the perceptual level, apprehensive and comprehensively to finally reaching the integrative level since it places emphasis on verification of the implementation of the strategies of leadership inserted to promote an organizational climate in which to work on the basis of a solid planning structured in where procedures are carried out in an equitable manner complying with a full and successful to the mission and vision of the campus and in this way to get results as a true team always committed to achieve the desired success demonstrating the interest arising from undertaking changes that provide enhancement to the system every day inserting quality indicators that provide guidelines for the big challenges that presents society.